Multiple Copies of a Simple MYB-Binding Site Confers Trans-regulation by Specific Flavonoid-Related R2R3 MYBs in Diverse Species - Brendolise, Cyril; Espley, Richard V.; Lin-Wang, Kui; Laing, William; Peng, Yongyan; McGhie, Tony; Dejnoprat, Supinya; Tomes, Sumathi; Hellens, Roger P.; Allan, Andrew C. (Frontiers in Plant Science, 2017)
In apple, the MYB transcription factor MYB10 controls the accumulation of anthocyanins. MYB10 is able to auto-activate its expression by binding its own promoter at a specific motif, the R1 motif. In some apple accessions a natural mutation, termed R6, has more copies of this motif within the MYB10 promoter resulting in stronger auto-activation and elevated anthocyanins. Here we show that other anthocyanin-related MYBs selected from apple, pear, strawberry, petunia, kiwifruit and Arabidopsis are able to activate promoters containing the R6 motif. To examine the specificity of this motif, members of the R2R3 MYB family were screened against a promoter harboring the R6 mutation. Only MYBs from subgroups 5 and 6 activate expression by binding the R6 motif, with these MYBs sharing conserved residues in their R2R3 DNA binding domains. Insertion of the apple R6 motif into orthologous promoters of MYB10 in pear (PcMYB10) and Arabidopsis (AtMY75) elevated anthocyanin levels. Introduction of the R6 motif into the promoter region of an anthocyanin biosynthetic enzyme F3′5′H of kiwifruit imparts regulation by MYB10. This results in elevated levels of delphinidin in both tobacco and kiwifruit. Finally, an R6 motif inserted into the promoter the vitamin C biosynthesis gene GDP-L-Gal phosphorylase increases vitamin C content in a MYB10-dependent manner. This motif therefore provides a tool to re-engineer novel MYB-regulated responses in plants.